(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the physiological changes that occur in the human respiratory and cardiovascular systems as a result of running exercises. Regular running scientifically highlights the importance of strengthening the respiratory heart muscles, increasing blood circulation efficiency, stabilizing blood pressure, and preventing heart diseases.